The Effect of Abdominoplasty and Outcome of Rectus Fascia Plication on Health-Related Quality of Life in Post–Bariatric Surgery Patients. Issue 6 (December 2015) - Staalesen, Trude; Olsén, Monika Fagevik; Elander, Anna
Abstract : Background: The authors prospectively evaluated the effect of isolated abdominoplasty with or without rectus fascia plication on the physical, functional, and psychosocial dimensions of health-related quality of life in post–bariatric surgery patients. They also evaluated whether the objectively measured amount of abdominal excess skin affects the discomfort of excess abdominal skin and changes in health-related quality of life after abdominoplasty. Methods: Ninety-four post–bariatric surgery patients answered questionnaires regarding their experience of excess skin and health-related quality of life before and 1 year after isolated abdominoplasty. An objective assessment of the amount of abdominal excess skin was also performed. All study participants were assigned randomly to either undergo or not undergo rectus fascia plication. Results: Significant improvements were reported at the follow-up concerning physical, functional, and psychosocial dimensions of health-related quality of life. A significant decrease was observed for the general health subscale of the 36-Item Short-Form Health Survey for the nonplicated group ( p = 0.039). No significant differences were observed between the plicated and nonplicated groups. A significant low correlation was identified between the change in the Short-Form physical function subscale after abdominoplasty and measured amount of excess abdominal skin ( r s = 0.26, p = 0.033) or resection weight ( r s = 0.20, p = 0.10). Conclusions: Isolated abdominoplasty in post–bariatric surgery patients seems to improve both physical and psychosocial dimensions of health-related quality of life. However, rectus fascia plication does not appear to influence health-related quality of life. In addition, the correlation between the objectively measured amount of abdominal excess skin and improvements in health-related quality of life after abdominoplasty in post–bariatric surgery patients appears to be low. CLINICAL QUESTION/LEVEL OF EVIDENCE: Therapeutic, II.